Effects of intermittent hypoxia on SaO2, cerebral and muscle oxygenation during maximal exercise in athletes with exercise-induced hypoxemia - Marshall, H. C.; Hamlin, M. J.; Hellemans, J.; Murrell, C.; Beattie, N.; Hellemans, I.; Perry, T.; Burns, A.; Ainslie, P. N. (European Journal of Applied Physiology, 2008)
In a placebo-controlled study, the effects of intermittent hypoxic exposures (IHE) or a placebo control for 10 days, were examined on the extent of exercise-induced hypoxemia (EIH), cerebral and muscle oxygenation (near-infrared spectroscopy) and VO2peak.VO2peak Eight athletes who had previously displayed EIH (fall in saturation of arterial oxygen (SaO2) of >4% from rest) during an incremental maximal exercise test, volunteered for the present research. Prior to (baseline), and 2 days following (post) the IHE or placebo, an incremental maximal exercise test was performed whilst SaO2, heart rate, cerebral and muscle oxygenation and respiratory gas exchange were measured continuously. After IHE, but not placebo, EIH was less pronounced at [VO2peak VO2peak (IHE group, SaO2 at VO2peak :VO2peak: baseline 91.23 ± 1.10%, post 94.10 ± 2.19%; P < 0.01, mean ± SD). This reduction was reflected in an increased ventilation (NS), a lower end-tidal CO2 (P < 0.01), and lowered cerebral TOI during heavy exercise (90% [VO2peak : - 6.1 ±6.0 \Updelta % ,\text P = 0.04). Unknown control sequence '\Updelta'Conversely, muscle tHb at maximal exercise, was increased (2.4 ± 1.8 µM, P = 0.01, mean ± 95 CL) following IHE, whilst de-oxygenated Hb at 90% of VO2peak VO2peakwas reduced (-0.9 ± 0.8 µM, P = 0.02). These data indicate that exposure to IHE can attenuate the degree of EIH. Despite a potential compromise in cerebral oxygenation, exposure to IHE may induce some positive physiological adaptations at the muscle tissue level. We speculate that the unchanged VO2peak VO2peakfollowing IHE might reflect a balance between these central (cerebral) and peripheral (muscle) adaptations.